Tržní oceňování podniku jako podklad pro strategická rozhodnutí - Karasová, Pavlína (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Předmětem diplomové práce je problematika tržního oceňování podniků. Teoretická část obsahuje základní pohledy a přístupy pro oceňování podniků. Představuje většinu používaných (i méně používaných) metod pro oceňování a doporučení pro jejich užití. Praktická část se již zabývá samotným oceněním společnosti na základě výnosové metody diskontovaných peněžních toků.

The subject of this Diploma thesis is problem of the Estimation of Company Market Value. Theoretical part contains elementary perspectives and possibilities for Estimation of the Company Market Value. This thesis presents most of using (so less using) techniques for evaluation end rocommendation for its using. Pracitical part includes estimation of real company market value by profit method of discounted cash flow.
Estimation of the Company Market Value for Strategical Statements
Keywords: Metody oceňování; hodnota; podnik; diskontované cash flow; finanční plán; Methods of valuation; value; company; discounted cash flow; financial plan